2005
DOI: 10.1007/s11178-005-0287-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Diisopropyl 6-Hydroxy-6-methyl-4-oxocyclohexane-1,3-dicarboxylates and Their Reactions with Nucleophilic Reagents

Abstract: Base-catalyzed reactions of isopropyl acetoacetate with aromatic and heterocyclic aldehydes afforded the corresponding diisopropyl 6-hydroxy-6-methyl-4-oxocyclohexane-1,3-dicarboxylates which were brought into reactions with mono-and difunctional nitrogen-containing nucleophiles. According to the X-ray diffraction data, diisopropyl 4-oxocyclohexane-1,3-dicarboxylates in crystal exist in the ketone form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…However, the heterocyclization reactions of β-cycloketols are not well studied. Thus, the literature describes the preparation of isoquinolines 2 [3][4][5][6][7], indazoles 3 [8][9][10], benzo[c]isoxazoles 4 [9,10], [1,2,4]triazolo [3-b]quinazolines 5 [11] and pyrazolo[3-c]isoquinolines 6 [12] (Scheme 1) by reactions of beta-cycloketols with various 1,2-and 1,3-dinucleophilic agents. Despite the large attention paid to reactions of aminoazoles with 1,3-dielectrophilic agents (see reviews [13,14]), only a few examples of reactions involving β-cycloketols were found in the literature.…”
mentioning
confidence: 99%
“…However, the heterocyclization reactions of β-cycloketols are not well studied. Thus, the literature describes the preparation of isoquinolines 2 [3][4][5][6][7], indazoles 3 [8][9][10], benzo[c]isoxazoles 4 [9,10], [1,2,4]triazolo [3-b]quinazolines 5 [11] and pyrazolo[3-c]isoquinolines 6 [12] (Scheme 1) by reactions of beta-cycloketols with various 1,2-and 1,3-dinucleophilic agents. Despite the large attention paid to reactions of aminoazoles with 1,3-dielectrophilic agents (see reviews [13,14]), only a few examples of reactions involving β-cycloketols were found in the literature.…”
mentioning
confidence: 99%
“…-индазол-5-карбоксилатов 83. Аналогичное взаимодействие с гидроксиламином приводит к оксимам 84, а с фенилгидразином -к гидразонам 85[30] (схема 31).…”
unclassified
“…Diacetyl-substituted cycloketols are known to react with hydrazine to form the corresponding indazoles [3]. The reaction of dialkyl 2-aryl-6-hydroxy-6-methyl-4-oxocyclohexane-1,3-dicarboxylates (Ia -m) with tosylhydrazide with heating in EtOH produced dialkyl 2-aryl-6-hydroxy-6-methyl-4-(p-toluenesulfonylaminoimino)cyclohexane-1,3-dicarboxylates (IIa -m) ( Table 1).…”
mentioning
confidence: 99%